MANAJEMEN PENDIDIKAN KARAKTER SISWA DI SEKOLAH DASAR - Hanafi Hanafi (UNIVERSITAS BENGKULU, 2015)
The objective of this research was to describe the management of student character education in elementary school, specific is to know about: the management plan, application andevaluation. The methode of this research is qualitative descriptive done within observation, documentation and interview. The result of this research show that: the first, the management plan had been done well by formulating objectives, strategic arrangement, deciding the policies,allocating Procedures, finance, and perfecting program; the second, the management application had been done well through the activities of organization and the application of students’ character values; the third, the management evaluation was applied through the oriented activitiesinto inspecting the program application, reflection, analysis and follow-up activitiesKeywords: management, students’ character, elementary school.